RESEPSI PEMBACA TERHADAP UNSUR FAKTA CERITA DALAM NOVEL AYAT AYAT CINTA KARYA HABIBURRAHMAN ELSHYRAZI - Munaris Munaris (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2011)
This study aims to describe readers’ reception of story fact elements (character, plot, and setting) in Ayat-Ayat Cinta (AAC). The data sources were reception texts uploaded by readers and were downloaded through Google. The data analysis and interpretation employed a combination of two perspectives, i.e. text reception and hermeneutics. The findings show that readers respond to the elements in the reception with positive and negative tones. In general, however, they respond to the elements positively. The characters that most readers respond to are Fahri, Aisha, Maria, and Nurul. Readers respond to the plot of AAC holistically, but most of them respond to only parts of the plot. They respond to two settings, i.e. spatial and social settings. Keywords: readers’ reception, story fact